Melayu Riau Language Defense through the Establishment of Language Lexical Innovation - Wagiati, Juli Yani, Wahya, Cece Sobarna, (Opción, 2019)
The purpose of this study was to determine the full lexical forms that experienced variations in the Malay language in Kampar district. This study used a descriptive method with refer, interviewing and recording. As a result, the most meaningful lexical field in Riau Malay in Kampar Regency is the meaning of the house and its surroundings, with a full lexical display of 6 full lexical. In conclusion, the retention of languages in Riau Malay in Kampar District, which experienced a full lexical form of innovation in Kampar District, was contained in 29 glossaries with 98 variants